Предмет: Алгебра,
автор: Freakazoid
Представьте в виде произведения:
3ax³ - 3ay³
Разложите на множители:
a³ + b³ - 2ab(a+b)
Ответы
Автор ответа:
0
3ax³-3ay³=3a(x³-y³)
a³ + b³ - 2ab(a+b)=(a+b)(a²-ab+b²)-2ab(a+b)=(a+b)(a²-3ab+b²)
Автор ответа:
0
3ax³-3ay³=3a(x³-y³)=3а(x-y)(x²+xy+y²)
a³ + b³ - 2ab(a+b)=(a+b)(a²-ab+b²)-2ab(a+b)=(a+b)(a²-3ab+b²)
Похожие вопросы
Предмет: История,
автор: israilfarzaliyev5
Предмет: Другие предметы,
автор: Аноним
Предмет: Алгебра,
автор: ratfromnarnia
Предмет: Математика,
автор: ваня6767